The Role of TRP Channels and PMCA in Brain Disorders: Intracellular Calcium and pH Homeostasis - Hwang, Sung-Min; Lee, Ji Yeon; Park, Chul-Kyu; Kim, Yong Ho (Frontiers in Cell and Developmental Biology, 2021)
Brain disorders include neurodegenerative diseases (NDs) with different conditions that primarily affect the neurons and glia in the brain. However, the risk factors and pathophysiological mechanisms of NDs have not been fully elucidated. Homeostasis of intracellular Ca2+ concentration and intracellular pH (pHi) is crucial for cell function. The regulatory processes of these ionic mechanisms may be absent or excessive in pathological conditions, leading to a loss of cell death in distinct regions of ND patients. Herein, we review the potential involvement of transient receptor potential (TRP) channels in NDs, where disrupted Ca2+ homeostasis leads to cell death. The capability of TRP channels to restore or excite the cell through Ca2+ regulation depending on the level of plasma membrane Ca2+ ATPase (PMCA) activity is discussed in detail. As PMCA simultaneously affects intracellular Ca2+ regulation as well as pHi, TRP channels and PMCA thus play vital roles in modulating ionic homeostasis in various cell types or specific regions of the brain where the TRP channels and PMCA are expressed. For this reason, the dysfunction of TRP channels and/or PMCA under pathological conditions disrupts neuronal homeostasis due to abnormal Ca2+ and pH levels in the brain, resulting in various NDs. This review addresses the function of TRP channels and PMCA in controlling intracellular Ca2+ and pH, which may provide novel targets for treating NDs.